Weed Control in Parsley - William M. Stall (EDIS, 2003)
Parsley is placed in the "leafy greens" EPA group due to its closeness to lettuce and spinach for residues. Bensulide may be applied to parsley preplant incorporated or preemergence on mineral soils. This document is HS952, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: August 2003.